Effect of Multiple Micronutrient Suplementation (MMS) in Pregnant Women on Anemia - Lestari, Lusi; Heryani, Heni (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2025)
Introduction: The nutritional needs of pregnant women increase 2-3 times as the gestational age increases. Fulfilling the dietary needs of pregnant women is a challenge, especially for low- and middle-income countries. Many pregnant women in poor countries experience micronutrient deficiencies. Micronutrient deficiencies can have a negative impact on pregnant women because they can cause problems for the health of the mother and fetus. The effect of deficiencies of micronutrients, namely iron, folic acid, and B12 in pregnant women is anemia. Iron deficiency anemia is one of the most common diseases during pregnancy. In addition to iron and folic acid supplements which are intended to anticipate anemia problems, pregnant women also need other micronutrient components in the form of vitamins and minerals. Multi Micronutrient Supplements (MMS) is one of the global strategies recommended by the United Nations International Childhood Emergency Fund (UNICEF) to prevent micronutrient deficiencies. Objective: The literature review aims to examine the benefits of consuming Multi Micronutrient Supplements (MMN) in overcoming anemia in pregnant women. Method: The method used in writing this article is a review of research results related to the provision of MMS to overcome anemia in pregnant women. Result: Based on the articles that have been analyzed, it can be seen that consuming MMN during pregnancy can increase hemoglobin levels so that it can prevent anemia in pregnant women. Conclusion: MMS consumption during pregnancy can increase hemoglobin levels and prevent anemia in pregnant women. Referring to this conclusion, it is recommended for pregnant women to consume MMS regularly.